Regression modelling combining MRI measurements and patient anthropometry for patient screening and prediction of graft diameter in hamstring autograft arthroscopic ACL reconstruction - Vincent V.G. An; Corey Scholes; Vikram A. Mhaskar; David A. Parker; Brett A. Fritsch (Elsevier, 2017)
Background: Previous studies have associated anthropometric data and pre-operative hamstring tendon measurements to intraoperative graft diameter for hamstring autograft ACL reconstruction, although an integrated model has yet to be described. The aim of this study was to present such a predictive model for quadrupled semitendinosus (4-ST) and doubled semitendinosus-gracilis (4-STG) graft constructs combining anthropometry (height and weight) and preoperative measurements of tendon as predictors. Methods: ACL reconstructions using 4-STG and 4-ST were retrospectively reviewed. The outlines of the semitendinosus and gracilis tendons were identified manually in the axial slice of a preoperative T2 weighted MRI using a region-of-interest tool. Regression analysis using intraoperative graft diameter as the dependent variable was performed with tendon cross-sectional area (XSA), gender and height as predictors. Results: 108 ACL reconstructions in 107 patients were examined, 75 of which were performed using the 4-STG construct, and 33 which employed the 4-ST construct. The mean graft diameter in the 4-ST group (8.6 ± 0.8 mm) was significantly (p < 0.001) greater than the 4-STG group (7.9 ± 0.7 mm). Female gender and 4-STG graft construct were associated with increased risk of graft diameter <8 mm. Predictive models of graft diameter were accurate to ±1 mm for both construct types. Conclusions: An integrated method for assessing patient risk of producing a diminutive graft diameter and planning augmentation in select cases has been presented. The present findings describe a validated predictive model that builds on previous univariable analyses. Further investigation of larger samples, including factors associated with graft preparation, is required to improve model accuracy for routine clinical application. Level of evidence: IV, Retrospective Cohort Study